KAJIAN TENTANG PENUNDAAN EKSEKUSI MATI BERDASARKAN INSTRUMEN HUKUM HAK ASASI MANUSIA INTERNASIONAL - Dhani Kristanto Utomo; Siti Muslimah; Handojo Leksono (BELLI AC PACIS, 2016)
This research purposed to get a legal argumentation related of the prolonged delays in the execution according to instruments of international human rights law. The question will be answered based on the norms and principles of international human rights law. The sources of this research are international conventions, doctrine, customary international law, publications, and national law in Indonesia. The legal sources collected by library research. The result show that the prolonged delays in the execution may violate Article 14 paragraph (3)c and Article 7 of the Covenant on Civil and Political Rights. There are so many countries, included Indonesia, have violated those articles.